Study the Correlation of Cutaneous Candidiasis and Some Immunity Parameters in Patients with Surgical Wound Infection - Hussein, Anmar Sael; Hasan, Thaer Abdullah; Alarim, Bushra Amir (American Journal of Biology and Natural Sciences, 2025)
Candida albicans is a type of opportunistic fungus that poses a significant concern to individuals with compromised immune systems. C. albicans is the source of the skin infection known as cutaneous candidiasis. The current work is aimed to study the effect of cutaneous candidiasis on some immunity parameters in patients with wound infection. The study was conducted in Kirkuk City from August 2023 to February 2024 and carried out on 120 patients admitted in the surgical wards of 3 hospitals of Kirkuk city. The different species of Candida were diagnosed by using a 10% KOH solution, Chrom agar culture and polymerase chain reaction (PCR). The study reported that 19 of 120 samples were found to be positive and 101 to be negative. It included the following types: C. albicans 13 (68.4%), C. tropicalis 4 (21.1%), and C. krusi 2 (10.5%). The results of PCR found that 13 (92.9%) of C. albicans isolates out of a total of 14 isolates possessed the ASL1 gene as a virulence factor. The IL-6 and IL-17 levels in serum of patients demonstrated significant increases in compared to the control group (3.85± 0.26) and (35.17 ± 3.94) respectively. For cluster of differentiation, CD8 and CD33 levels in serum of patients demonstrated significant increases compared to control (295.11± 25.04), (81.64 ± 7.74), respectively. In Conclusion, cutaneous candidiasis led to changes in some immune parameters, and it was found that interleukins and CD markers play an important role in protection against candidiasis infections.